Living donor liver transplantation for congenital absence of portal vein in portal venous reconstruction with a great saphenous vein graft - Peilin Li; Masaaki Hidaka; Takashi Hamada; Satoshi Ikeda; Shinichiro Ono; Yasuhiro Maruya; Tota Kugiyama; Takanobu Hara; Tomoko Yoshimoto; Tomohiko Adachi; Takayuki Tanaka; Takayuki Miyoshi; et al. (Surgical Case Reports)
Abstract Background Congenital absence of portal vein (CAPV) is a rare structural anomaly in which the portal vein (PV) blood that normally flow into the liver directly drains into the systemic venous system through other collateral circulation. Congenital portal vein shunts (CPSs) is classified into types I and II according to the absence or presence of the intrahepatic portal vein, respectively. The CPS type I is also known as CAPV. The liver transplantation may be the only treatment option for CAPV. The key point of liver transplantation for CAPV is the reconstruction of the PV. Case presentation A 29-year-old man was diagnosed with CAPV with splenomegaly and gastroesophageal varix when being treated for pancytopenia and liver dysfunction. A living donor liver transplantation was performed for him using the right lobe which had been donated by his mother. The PV was reconstructed using his own great saphenous vein (GSV) as a graft vein. The end of the GSV graft was anastomosed to the inferior mesenteric vein while the other end was anastomosed to the vein graft of the right hepatic vein from the explanted liver. Conclusion Using the patient’s own GSV for PV reconstruction during living donor transplantation in the patient with CAPV seems to be an effective method.